(untitled) (Proceedings OPTIMAL, 2024)
All countries will experience population aging and this will continue to happen in the next few years. One of the psychological changes that often occur in the elderly is anxiety. The purpose of this study was to determine the effect of Javanese gamelan music therapy on anxiety in the elderly. The method used was a scoping review using the Google Scholar database. The keywords used were "elderly" AND " gamelan music therapy " OR "javanese gamelan music therapy " OR " balinese gamelan music" AND "anxiety ". Inclusion criteria included full-text articles from 2019-2024 in Indonesian or English published from national or international journal. The types of articles were Randomized Controlled Trial (RCT), Quasi Experimental, and Case Study. Five articles met the inclusion criteria. After reviewing the articles, we conclude that there is an effect of gamelan music therapy on reducing anxiety in the elderly.